2020
DOI: 10.1536/ihj.19-301
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Bystander Cardiopulmonary Resuscitation and Dispatcher Assistance on Survival After Out-of-Hospital Cardiac Arrest Among Adult Patients by Location of Arrest

Abstract: We investigated the impact of bystander-initiated cardiopulmonary resuscitation (CPR), dispatcher assistance (DA), and location of arrest on survival and outcomes after out-of-hospital cardiac arrest (OHCA). From a nationwide population-based registry of OHCA patients in Japan, we enrolled adult patients with bystander-witnessed OHCA of medical origin between 2013 and 2015. The primary outcome measure was a neurologically favorable outcome, defined by cerebral performance category 1 or 2. Multivariable logisti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
13
0
6

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 34 publications
2
13
0
6
Order By: Relevance
“…The study showed that the greatest influence on the return of spontaneous circulation concerning ineffective resuscitation was observed when ventricular fibrillation or pulseless ventricular tachycardia was observed as the first monitored cardiac arrest rhythm (odds ratio = 0.43; 95% CI 0.18-1.04). This is also confirmed by numerous studies [25,26].…”
Section: Discussionsupporting
confidence: 85%
“…The study showed that the greatest influence on the return of spontaneous circulation concerning ineffective resuscitation was observed when ventricular fibrillation or pulseless ventricular tachycardia was observed as the first monitored cardiac arrest rhythm (odds ratio = 0.43; 95% CI 0.18-1.04). This is also confirmed by numerous studies [25,26].…”
Section: Discussionsupporting
confidence: 85%
“…The other study showed that the AORs of BCPR without and with dispatcher assist were 1.44 (95% CI: 1.22-1.70) and 1.60 (95% CI: 1.45-1.77) on neurologic recovery, respectively, compared with no BCPR in private places. Additionally, they were comparable to 1.43 (95% CI: 1.24-1.65) and 1.62 (95% CI: 1.43-1.85) in public places [33]. There would be no conflict with the present study even if the BCPR effect was higher in public places in other studies because the outcome estimates in our study were obtained from models considering the interaction between confounding variables, unlike those in other studies.…”
Section: Discussionsupporting
confidence: 47%
“…These findings seem to be contrary to the previous studies reporting poor outcomes of OHCA at private places. However, few studies have directly demonstrated a variation in the effect of BCPR on the outcomes of OHCA based on place, while at-home OHCA is well known to have a poorer prognosis than OHCA at public place [32,33]. A study revealed that BCPR provision and neurologic recovery increased by 2.45-and 1.51-fold in the daytime if friends witnessed OHCA compared with those if family members witnessed OHCA (95% CI: 2.31-2.58, 95% CI: 1.36-1.68) [32].…”
Section: Discussionmentioning
confidence: 99%
“…(1) As chaves para o tratamento da PCR sĂŁo o reconhecimento precoce, o acionamento do serviço mĂ©dico de emergĂȘncia, o inĂ­cio das compressĂ”es torĂĄcicas e a desfibrilação precoce. (2,3,4) Os quatro passos descritos anteriormente sĂŁo considerados procedimentos de baixa complexidade, entretanto, a população brasileira nĂŁo recebe treinamentos periĂłdicos para reconhecer e conduzir as compressĂ”es torĂĄcicas atĂ© a chegada da equipe de emergĂȘncia. As consequĂȘncias geram baixas taxas de sobrevida que perpassam entre 1% parada cardĂ­aca BrandĂŁo, P.C.…”
unclassified
“…(2) InstruçÔes adequadas pelo despachante, ao telefone, e parada cardĂ­aca assistida demonstram resultados promissores em locais pĂșblicos. (4) A continuidade da assistĂȘncia se dĂĄ, estrategicamente, com a chegada da equipe do SAMU, que inicia o atendimento com a realização de Suporte BĂĄsico e Avançado de Vida. O objetivo Ă© aumentar a sobrevida do paciente, com a realização de intervençÔes precoces como a manutenção de compressĂ”es torĂĄcicas efetivas, uso de via aĂ©rea avançada, medicaçÔes especĂ­ficas para cada caso, e, com o sucesso da reanimação, encaminhamento para uma unidade hospitalar que possa dar continuidade ao tratamento.…”
unclassified